Mitochondrial DNA variability in the Czech population, with application to the ethnic history of Slavs - Malyarchuk, Boris A; Vanecek, Tomas; Perkova, Maria A; Derenko, Miroslava V; Sip, Miroslav (Human biology, 2006)
Mitochondrial DNA (mtDNA) variability was studied in a sample of 179 individuals representing the Czech population of Western Bohemia. Sequencing of two hypervariable segments, HVS I and HVS II, in combination with screening of coding-region haplogroup-specific RFLP markers revealed that most Czech mtDNAs belong to the common West Eurasian mitochondrial haplogroups (H, pre-V HV*, J, T, U, N1, W, and X). However, about 3% of Czech mtDNAs encompass East Eurasian lineages (A, N9a, D4, M*). A comparative analysis with published data showed that different Slavonic populations in Central and Eastern Europe contain small but marked amounts of East Eurasian mtDNAs. We suggest that the presence of East Eurasian mtDNA haplotypes is not an original feature of the gene pool of the proto-Slavs but rather may be mostly a consequence of admixture with Central Asian nomadic tribes, who migrated into Central and Eastern Europe in the early Middle Ages.
Keywords: Europe, Eastern; populační skupiny; haplotypy; Humans; východní Evropa; populační genetika; Polymorphism, Restriction Fragment Length; mitochondriální DNA; Genetics, Population; DNA, Mitochondrial; frekvence genu; Haplotypes; Ethnicity; lidé; genetická variace; Genetic Variation; Czech Republic; Gene Frequency; etnicita; genetické testování; polymorfismus délky restrikčních fragmentů; Genetic Testing; Česká republika; Population Groups